Preliminary analysis of quality of life (QOL) before and after surgery for female genital fistula. A prospective cohort study (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To describe the characteristics of women who come for repair of FGF, assess their QOL before & after surgery and estimate factors associated with improved quality of life.Methods: All women who came to LAMB for FGF repairin 2016 and 2017 were interviewed on admission and called for a follow-up visit 6 months after successful surgery. Sociodemographic, obstetric, and fistula-related information was collected on admission. Health related QOLwasmeasured using the 36-item short form (SF-36), and perception of stigma and discrimination were assessed on admission and at follow-up.Results: A total of 72 women were included.Mean age was 40.1 years, 49% had no education, and 42% were in the poorest wealth quintile.The mean stigma score (out of 7)went from 3.79 to 1.40 post surgery (p